In Situ, Ex Situ and On Farm Conservation of Plant Genetic Resources in Neotropics - Monteiro Siqueira, Marcos Vinicius Bohrer; Costa, Flaviane Malaquias; Boaventura Novaes, Carolina Ribeiro Diniz; Bustamante, Patrícia Goulart; De Moraes Silvestre, Marcela Aparecida [UNESP] (Springer Nature, 2023)
The prospect for the coming decades will be for humanity to witness a holocaust of species on Earth. Within these species are plants for food purposes undergoing genetic erosion and, putting at risk not only their own existence, but the safety of human life. Several genetic tools have been used in recent years to support breeding and conservation programs. Diverse agendas, from countless countries, endeavored to drive ex situ, in situ conservation, and the sustainable use of genetic resources for food and agriculture. Brazil, an example of country with a rich agrobiodiversity in Neotropics, has advanced in research and appreciation of plant genetic resources, however at the same time it has led vast biological losses. In this chapter, we will review some concepts related to plant genetic resources, present case studies for in situ, ex situ and on farm conservation and discuss some recommendations to safeguard the valuable genetic inheritance of food plants.